1975
DOI: 10.1007/bf01544269
|View full text |Cite
|
Sign up to set email alerts
|

Age and perceived effects of erotica-pornography: A national sample study

Abstract: In the spring of 1970, a national sample survey of 2486 adults (aged 20-80) was studied to ascertain U.S. public attitudes toward and experience with erotic materials. Twelve items measured whether or not those interviewed believed that looking at or reading sexual materials had certain effects on themselves or others. Initial description of the results revealed a considerable diversity of opinion. This report provides a multistage typology of those item responses, beginning with characterization of items as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…While a possible doubling in pornography viewing may be related to more favorable attitudes toward women, another explanation is that attitude favorability toward women increases with age. This is consistent with the findings of Merritt, Gerstl, and Lo Scuito (1975), who noted that attitudes toward pornography became more positive as age increased. Their explanation is also consistent with the findings of Study 2: Age and attitude (Total Score) were positively and moderately related, r (17) = .…”
Section: Discussion Of Studies 1 Andsupporting
confidence: 93%
“…While a possible doubling in pornography viewing may be related to more favorable attitudes toward women, another explanation is that attitude favorability toward women increases with age. This is consistent with the findings of Merritt, Gerstl, and Lo Scuito (1975), who noted that attitudes toward pornography became more positive as age increased. Their explanation is also consistent with the findings of Study 2: Age and attitude (Total Score) were positively and moderately related, r (17) = .…”
Section: Discussion Of Studies 1 Andsupporting
confidence: 93%
“…The current affective changes in response to the erotic film are inconsistent with the observation of Merritt and colleagues (1975) that women's attitudes toward erotica become increasingly intolerant with age. However, the use of female-oriented erotic material has been common practice for only the past decade and may explain why studies published in the 1970s and 1980s, which employed male-oriented erotica, reported negative affective responses in older women (Merritt et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The nding of little difference in responses between age groups contrasts with several earlier studies where younger people have been reported as nding sexually explicit material more acceptable than older people (Barnett & Thomson, 1996;ITC, 1996;Diamond & Dennemiller, 1989;Merritt et al, 1975). Barnett & Thomson (1996) reported that age was the strongest factor in uencing responses to sexually explicit material.…”
Section: Discussionmentioning
confidence: 59%